RANCANG BANGUN ALAT PENGHITUNG BIBIT IKAN LELE BERBASIS MIKROKONTROLER - Engla Desita; Endah Fitriani (Politeknik Piksi Ganesha Indonesia, 2025)
Catfish farming in Indonesia has significant potential; however, conventional methods of counting fish fry still face various challenges, such as the considerable time required and a high risk of errors. This study aims to design and build an automatic counting device for catfish fry based on the Arduino Mega 2560 microcontroller, integrated with an E18-D80NK infrared proximity sensor and a DS18B20 temperature sensor. The device is specifically designed to count catfish fry measuring between 6 to 8 cm, where the infrared proximity sensor is used to count the number of fish fry passing through, while the DS18B20 sensor functions to detect the water temperature in the holding tank. The operational process of the device includes inputting the number of fry via a 4x4 keypad, opening the counting path using a servo motor, measuring the water temperature, displaying data on a 16x2 LCD, and closing the path after the counting process is completed. The test results indicate that the DS18B20 sensor has an accuracy of 97.68% with an average error of 2.32%, while the infrared proximity sensor achieves an accuracy of 89.08% with an average error of 10.92%. This device successfully counts the number of catfish fry automatically, monitors the water temperature, and displays information in real-time on the LCD. Therefore, the catfish fry counting device based on the Arduino Mega 2560 is expected to enhance time and labor efficiency, as well as minimize errors in the counting and distribution processes of catfish fry.